Bones! - Shipton, Paul (Oxford Oxford University Press, 2014)
The school trip to the museum is going badly for David in Bones!. Chris, the class joker, is annoying him with daft jokes. But now something is really wrong. Something terrifying is on the loose... TreeTops Fiction contains engaging novels from top authors and illustrators with the variety children need to develop a love of reading!
Include Illustrations
Keywords: Dinosaurs -- Welsh language